Factors that Affect the Improvement of Students’ Speaking Skills through Group Discussion Technique: A Case Study at Vocational High School 5 Gowa - Ananda Rahmadana; Abidin Pammu; Nasmilah Nasmilah (Hasanuddin University, 2023)
The present study aimed to investigate the factors that affected the improvement of students’ speaking skills through group discussion technique at Vocational High School 5 Gowa. To carry out the phenomena, this study employed a descriptive qualitative methodology. The data were collected by using semi-structured interviews to obtain the deepest data about the factors that affected the improvement of students’ speaking skills through discussion technique at Vocational High School 5 Gowa. The populations were all classes in second grade, and then the samples were two classes that were chosen deliberately or purposively through nonprobability sampling. From the two classes, the participants were comprised of twenty (20) students, and each class involved 10 students. To analyze the data, this study used a thematic analysis process to discover the themes or factors that emerged as the data later. The results revealed that there are seven factors as themes appeared in this study, they are cohesiveness, conformity, roles, goals, charismatic leadership, inspiration, and competition and conflict factors. In conclusion, the seven factors assisted the students in improving their speaking skills; such as conveying ideas freely, having good confidence in speaking, and learning to respect other members’ ideas. The finding of this study can encourage English teachers at vocational school to use group discussion technique in their English classes to reach better teaching speaking skills improvement of the students.